Study of Iron and Calcium Removal on Manganese Sulfate Precursors for Battery Cathode Raw Material Applications - Hakim, Agsel Fauzia; Andriyah, Lia; Oediyani, Soesaptri; Lalasari, Latifa Hanum; Sulistiyono, Eko; Irawan, Januar; Arini, Tri; Yunita, Fariza Eka; Suharyanto, Ariyo; Setiawan, Iwan; Firdiyono, Florentinus; Yuwono, Akhmad Herman (Metalurgi, 2024)
Global battery sales are expected to reach $310.8 billion in 2027, up 14.1% from 2020. 95% of the world's batteries are lead-acid, lithium-ion, or nickel-based. One of the most popular batteries on the global market is lithium-ion, which uses MnSO4 powder as its cathode raw material. Manganese sulfate-based lithium-ion batteries can be made using Indonesian resources, specifically manganese ore from Trenggalek. Trenggalek manganese ore is of poor quality and contains impurities, primarily Fe and Ca. To produce 98% powder manganese sulfate, the solution is prepared, reduced with briquette charcoal, leached, precipitated, carbonated, and crystallised. NH4OH reagent is used to remove Fe through precipitation, and the carbonatation process is employed to eliminate Ca, resulting in 97.237% purity of manganese sulfate powder product. This outcome is achieved under precipitation process conditions of [NH4OH 2M], T = 80 °C, pH = 4, t =180 minutes, while carbonatation process conditions are T=50 °C, t = 120 minutes.